Portable laminar flow hood - Choy, Hiu Fung. (2013)
Health care to the fortunate ones usually mean accurate diagnostic tests using state-of-art technology, effective medication and highest standard of hospital services. However, for people living in developing countries (third world countries), they may not even have the chance to afford basic medication. This is due to them living in poverty without the assistance of their governments to ensure everyone receives basic health care services. Also these clinics/hospitals does not have the ability to provide the standard environment for its patients. There are no air-condition and neither are there window panels to isolate the premise and thereby resulting in the compromisation of hygiene level around the compound. Such level of condition creates a reservoir for contaminants to stay adrift in space and causes harmful effects towards the patients.